Analisis Pengaruh Digital Marketing Terhadap Brand Awareness Produk X di PT. XYZ Studi Kasus pada Sosial Media Instagram @Xid di Kota Bandung - Nur Hafizah Kusuma Astuti; Dewi Anggraeni, Angga; Adjane Annisawati, Asaretkha (Jurnal Manajemen dan Bisnis Kreatif, 2024)
This research aims to examine the influence of Digital Marketing on Brand Awareness ofSanlex products in Bandung. Using quantitative methods with descriptive and associativeapproaches, data was collected through questionnaires and literature study. Data analysiswas carried out using SPSS 25 and incidental sampling technique with 384 respondents. The results of the descriptive analysis show that the average for the Digital Marketingvariable is 4.35 and Brand Awareness is 4.36, both in the "Very Good" category. Hypothesistesting shows that Digital Marketing has a positive effect on Brand Awareness with acalculated t value of 14.759 > t table 1.966 and a significance of 0.000 < 0.05.Simultaneously, Digital Marketing has a positive effect on Brand Awareness with acalculated F value of 217.83 > F table 3.87 and a significance of 0.000 < 0.05. The R2 valueof 0.363 indicates that 36.3% of the variation in Brand Awareness is explained by DigitalMarketing, while the remaining 63.7% is influenced by other factors that were not studied.